Yerel Tarih Öğretim Yöntemini Sosyal Bilgiler Dersinde Kullanmak: Yanı Başında Olan Geçmişi Görmek ve Duyumsamak. - ÖZTAŞÇI, Cemile Ayça; KABAPINAR, Yücel; TUNCEL, Gül (Turkish History Education Journal (TUHED))
Certain changes in Social Studies education have brought along new methods of instruction and new teaching techniques. Together with these changes, in accordance with the new Social Studies teaching approach, a variety of methods that enable students to actively engage in learning have come into prominence. As one of these methods, local history has gained wider acceptance in the Social Studies Curriculum as a method that provides an opportunity for students to establish a connection between the past and the present within the framework of the concepts of change and continuity. It has been observed that despite being in the curriculum, local history has been limited in application and could not go beyond field trips to museums or historical places. The purpose of this study is to show how the local history teaching method can be applied in Social Studies lessons, to identify the benefits of this method in learning and to determine the problems faced during this process. This hereby is a qualitative research and has been modeled as action research. The working group comprises of 22 students that study in the 6th grade of a private middle school. The research was conducted in an 11-week period. During this study, researcher and student journals, student projects, student project evaluation questionnaires have been used in order to collect data. Student project evaluation questionnaires were analyzed through content analysis. Data collected from researcher and student journals were analyzed through descriptive analysis. Student projects were evaluated through a 'Local History Project Assessment Rubric' that was prepared by the researcher. Following a local history education that came into being under the title "Little Historians Trace the Past in the Present: A Local History Project," students have adopted roles as little historians and completed the phases that comprised of steps such as determining a subject, making research, conduction verbal history interviews, preparing reports and exhibition. Historical Turkish Delight Manufacturer Haji Bekir (Bahçekapı, 1777), Pandeli Restaurant (Eminönü, 1901), Kanaat Restaurant (Üsküdar, 1933), local Bitlis dishes, the traditional clothes of Macedonian Turks, Elmalı Konak (Boyralar Village, Elmalı, Antalya), are some of the issues which students researched in the local history project. In conclusion, students' perception of history and local history before and after the research has shown a relative difference. It was found that the students have achieved a success rate of 81% in the local history projects that they have conducted. The research findings show that the students have encountered various problems during the local history project, yet the local history teaching method has contributed positively to the academic, personal and social development of students as reported by the students, parents and the researcher.